Software Defined Radio: Basic Principles and Applications - Machado-Fernández, José Raúl (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The author makes a review of the SDR (Software Defined Radio) technology, including hardware schemes and application fields. A low performance device is presented and several tests are executed with it using free software. With the acquired experience, SDR employment opportunities are identified for low-cost solutions that can solve significant problems. In addition, a list of the most important frameworks related to the technology developed in the last years is offered, recommending the use of three of them.